Time and Cost Control Analysis of Disaster Emergency Response Handling Project Construction in Mojokerto District Using Critical Path Method - Nurrahmat, Ean Fadhillah; Wulandari, Esti; Nugroho, Laksono Djoko (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Landslides along the Sumber Pasinan River in Mojokerto Regency, East Java, pose significant risks due to soil erosion and increased flooding during the rainy season. This study aims to analyze the acceleration of construction for a disaster emergency response project using the Critical Path Method (CPM) to minimize time and costs. Employing a quantitative research approach, primary data was gathered through direct observations at the project site, complemented by secondary data from relevant literature and project documents. The findings indicate that the implementation period was successfully reduced from 71 working days to 47 days, achieving a time acceleration of 24 days. This required the addition of 11 workers for the critical task of installing river stone masonry, which constituted 70.16% of the project's workload. The application of CPM proved effective in managing time and resources efficiently. The implications of this research highlight the importance of employing structured project management methodologies in disaster response construction projects. By demonstrating the effectiveness of CPM in accelerating project timelines while controlling costs, this study provides a valuable reference for future projects facing similar challenges. It also opens avenues for further research into the long-term impacts of workforce augmentation on project quality and cost-effectiveness in disaster management contexts.